Changing Urban Scenario in Haryana - 2001-2011: A Spatial Analysis: Exploring Urban Development and Remote Sensing in Haryana: A Case Study of Ahmedabad (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The investigation of urban zones and their advancement centers around urban communities, their physical and statistic extension and the pressures and effects that accompany urban development. Particularly in creating nations and developing national economies like India, predictable and cutting-edge data or other arranging important information very regularly isn't accessible. With its Brilliant Urban areas Mission, the Indian government places extraordinary significance on the future advancements of Indian urban zones and pays tribute to the huge scale rustic to urban movement. The possibilities of urban remote detecting and its commitment to urban arranging are talked about and identified with the Indian Keen Urban communities Mission. A contextual investigation is exhibited indicating urban remote detecting based data items for the city of Ahmedabad. Coming about urban development situations are introduced, hotspots distinguished and future activity choices proposed.